6. INPATIENT EXPERIENCE OF NUTRITIONAL AND ENVIRONMENTAL CARE IN THE SURGICAL DEPARTMENT VINMEC TIMES CITY INTERNATIONAL GENERAL HOSPITAL IN 2021 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2024)
Objective: Describe patient experiences regarding nutritional and environmental care at the Surgery Department of Vinmec Times City International General Hospital in 2021 and some related factors. Methods: Cross-sectional description of 228 patients, data collected through the experience assessment toolkit of the US Healthcare Quality Research Agency.Results: The percentage of patients with positive experiences about nutritional care activities is quite high 89.5%, 3.5% of patients have negative experiences with service staff, 3.5% of meals were not hot and 3.9% of meals were not on time. The proportion of patients with positive experiences about the hospital environment is 86.4% and 13.6% are not positive, of which 9.7% have inpatient facilities that meet their needs. Patients with a hospital stay of less than 2 days experienced positive nutrition care 3.5 times more likely to have a hospital stay of more than 2 days. Self-funded patients had fewer positive nutritional experiences than insurance co-pays (p
Keywords: Experience, nutrition, patients, environment.